Bandwith conservation framework for mobile cloud computing: challenges and solutions - Olanrewaju, Rashidah Funke; Egal, Abdallah; Khalifa, Othman Omran (2014)
Mobile devices are rapidly transforming the computing industry. It is emerging to be the super future computers. Challenges including network bandwidth limitation, availability and storage are among the limitations facing MCC as the number of mobile devices accessing the cloud services are rapidly growing. This paper reviews the state of art of mobile cloud computing as well as it summarizes the latest MCC challenges and solutions. We will also propose a bandwidth conservation framework that will help the bandwidth constrained users to reschedule bandwidth allocation